Effectiveness of Behavioral Counseling with Modeling Techniques to Improve the Self-achievability - Komang Tri Paramitha Anggreni; I Ketut Dharsana; Kadek Suranata (International Conference on Technology and Educational Science)
This study aims to determine the effectiveness of behavioral counseling modeling techniques to improve the characterget things done well and will succeedthrough lesson study on first-grade students. This type of research is quasi-experimental with pre-test and post-test control group design. This study population of 58 students, while the samples of this study are 22 students, Collecting data using questionnaires character get things done well and will succeed with 30 items. The results of the data analysis tcount value 22.48> ttable 2,07 so that Ho refused and Ha accepted. So there is a significant difference. It can be concluded that effective behavioral counseling modeling techniques to improve the characterget things done well and will succeed.